CANDESARTAN REVERSES MEMORY DEFICIT CAUSED BY COLCHICINE INDUCED CHOLINERGIC DYSFUNCTION AND OXIDATIVE STRESS - Awasthi, Himani; Siddiqui, H. H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: We sought to investigate the protective activity of candesartan against memory impairment, oxidative stress and cholinergic dysfunction induced by activation of the central renin-angiotensin system. Methods: Male Swiss albino mice were divided into eight groups. Group 1 received vehicle (1.0% w/v gum acacia), orally for 14 d. Group 2 received intracerebrally (i. c.) artificial cerebrospinal fluid (aCSF, the vehicle of colchicine) and treated with vehicle for 14 d. Group 3, 4 and 5 injected with i. c. colchicine in the doses of 1µg, 2µg, 3µg respectively and treated with vehicle for 14 d. Group 6 and 7 received i. c colchicine (3 µg) and treated with candesartan (0.05 and 0.1 mg/kg respectively) orally for 14 d. Group 8 received i. c colchicine (3 µg) and treated with standard drug donepezil 5 mg/kg (PO) for 14 d. Learning and memory behavior was assessed by using morris water maze. Biochemical parameters of oxidative stress and cholinergic function were estimated in the brain on day 18. Parameters of oxidative stress and cholinergic function were estimated after the completion of behavioral studies Results: Treatment with a higher dose of colchicines (3µg/mice) caused memory deficit as shown by no significant decrease in escape latency time throughout all the sessions. Results of biochemical estimation showed a marked increase in malondialdehyde (MDA), nitrite level, reduced glutathione (GSH) level, cholinotoxic effect of colchicines has been correlated by marked decrease in acetyl cholinesterase (AChE) activity. Colchicine in a dose of 3 µg/mice has been validated. Pretreatment with candesartan in doses 0.05 and 0.1 mg/kg reverses oxidative stress which can be measured by decreased MDA, nitrite level and increased GSH level. Increased AChE activity may imply protection of cholinergic neurons hence improvement in learning and memory behavior. Conclusion: Preventive treatment with angiotensins receptor blocker, candesartan showed that memory impairment induced by colchicines may be mediated by alteration of central rennin angiotensins system and loss of cholinergic neurons. This study highlighted a number of clinical findings which support marked neuroprotection by blocked of the central AT1 receptor.